Equality as the Name of Democracy - Bratina, Boris R. (Sociološki pregled, 2019)
This exceptional book for our public opens dilemmas about the potential of democracy as it is, an opinion which is frequently taken for granted or rejected here, in a rather arbitrary manner. In contrast, both in structuralism and in its “post” stage there is also extreme strictness of opinion which is observed by the author throughout her presentation. The author does not choose to present the view from this point of view by sole discretion, but instead, in our opinion, does it because such perspective ensures meaningful alternatives in relation to the idea and actuality of (essentially totalitarian) (neo)liberal democracy. On the whole, this is a book by the author mature in political philosophy, the author with an attitude, whose detailed and reliable analysis brings to light the burning questions of contemporaneity.Keywords: democracy, representative democracy, equality, direct democracy, universality.